A High‐Capacity, Long‐Cycling All‐Solid‐State Lithium Battery Enabled by Integrated Cathode/Ultrathin Solid Electrolyte. Issue 35 (28th July 2021) - Lin, Yanke; Wu, Maochun; Sun, Jing; Zhang, Leicheng; Jian, Qinping; Zhao, Tianshou
Abstract: Current all‐solid‐state lithium battery (ASSLB) manufacturing typically involves laborious fabrication and assembly of individual electrodes and solid electrolyte, which inevitably result in large interfacial resistances. Moreover, due to the unfavorable mechanical strength, most solid electrolytes are fabricated to be overly thick and are incapable of retarding lithium dendrite formation. These factors limit the attainable energy density and cyclability of ASSLBs. Here, a novel integrated cathode/solid electrolyte for scalable ASSLB manufacturing is reported by directly fabricating an ultrathin yet robust fiber network reinforced solid electrolyte on the cathode. The integrated design allows continuous ion conduction at both the interface and the entire cathode, thereby considerably reducing interfacial resistance and enabling higher cathode loading. Meanwhile, the strong fiber network endows the solid electrolyte with an ultrasmall thickness and superior dendrite suppression capability. As a result, the newly‐developed Li/LiFePO4 ASSLB achieves a high capacity of 155.2 mAh g –1 at 0.5 C and 45 °C with capacity retention of 84.3% after 500 cycles. Even with a cathode loading of 13 mg cm –2, the battery still delivers a capacity of 124.1 mAh g –1 . Additionally, a pouch cell with this integrated design displays good electrochemical performance and safety, showing great promise for practical applications. Abstract : To overcome the limitations of conventional all‐solid‐state lithium battery (ASSLB) manufacturing, a novel integrated cathode/solid electrolyte is reported by directly fabricating an ultrathin yet robust solid electrolyte on the cathode. This work provides a new, scalable strategy for manufacturing advanced ASSLBs that exhibit high energy density and high cyclability.